UPAYA MENINGKATKAN HASIL BELAJAR IPAS MELALUI MODEL PROBLEM-BASED LEARNING MATERI WUJUD ZAT DAN PERUBAHANNYA - Adeliyani, Zhavira; Kusumawati, Mustika (Prodi Pendidikan Guru Madrasah Ibtidaiyah, 2024)
The purpose of this study was to evaluate the development of student learning outcomes, teacher and student activities, the teacher's ability to direct learning and student responses to the application of problem-based learning (PBL) in the learning process. This type of research is Classroom Action Research (CAR). The subjects of this study were class IV students of SD Negeri 02 Gejlig for the academic year 2022/2023, which consisted of 5 students. In this study, observation sheets, tests and questionnaires were used as data collection tools which were analyzed using descriptive statistics. The results showed that (1) the percentage of individual total perfection increased from Cycle I to Cycle II, namely 60% to 100%, as well as the percentage of total classical perfection increased from 50% to 100%. (2) The activity of teachers and students increases during the learning process. (3) the teacher's learning management skills increased from the adequate category to the good category. (4) Student responses were generally positive, with 100% of students saying they enjoyed learning using this constructive problem-based learning (PBL) model. From this study it can be concluded that the application of the Problem-based Learning (PBL) learning model can improve the science learning outcomes of fourth grade students at SD Negeri Bagi 01 regarding the material form of matter and its changes.